Anthem critical thinking and writing skills an introductory guide - Ehrhardt, Victoria Pontzer; ebrary, Inc. (London ; New York : Anthem Press, 2011)
" Anthem Guide to Critical Thinking Skills: Language and Logic' guides readers in the process of critical thinking and persuasive speaking and writing. The text discusses informal thinking, the formal processes of induction, deduction, and syllogistic reasoning, in a clear format that makes it easy for the "beginning logician" to process. Students learn how to form a proposition, identify issues, gather evidence, and process an argument. To get started, logic games, puzzles, and real life examples ask students to consider how we evaluate, analyze, and decide. What happens if Janie says, 'Mom, can I go to the party? All of my friends are going!' And Mom responds, 'What if all of your friends jumped off the empire State building?' Is 'all of my friends are going' a good reason? Does mom have a point? Language and Logic will help students evaluate these everyday decisions. Then a more formal look at induction and deduction challenges students to practice higher-level thinking skills, such as using analogies for evaluation, and working through syllogisms to process ideas. After a review of the Greek Fallacies, readers can have some literary logic fun by analyzing old standards like 'Love is a Fallacy' and the persuasive love poem 'The Passionate Shepherd'"-- Provided by publisher.
Machine generated contents note: Introduction to Critical Thinking What is Argument? Research and Evidence Inductive Reasoning Deductive Reasoning The Classical Fallacies Reasoning Through the Ages Putting It All Together -- A Research Project Appendix 1: Answers for Practice Exercises and chapter Reviews Appendix 2: Logic Test Appendix 3: Answers for Logic Test Appendix 4: Persuasive Paper Rubric.
Includes index.
Electronic reproduction.
Keywords: English language -- Composition and exercises -- Study and teaching (Secondary); English language -- Rhetoric -- Study and teaching (Higher); Critical thinking -- Study and teaching (Secondary); Critical thinking -- Study and teaching (Higher); Electronic books